Tracing disinfection byproducts in full-scale desalination plants - Le Roux, J.; Nada, N.; Khan, M.; Croue, Jean-Philippe (Elsevier BV, 2015)
© 2014 Elsevier B.V. The aim of this study was to assess the formation and the behavior of halogenated byproducts (regulated THMs and HAAs, as well as nitrogenous, brominated and iodinated DBPs including the emerging iodo-THMs) along the treatment train of full-scale desalination plants. One thermal multi-stage flash distillation (MSF) plant and two reverse osmosis (RO) plants located on the Red Sea coast of Saudi Arabia. DBPs formed during the prechlorination step were efficiently removed along the treatment processes (MSF or RO). Desalination plants fed with good seawater quality and using intermittent chlorine injection did not show high DBP formation and discharge. One RO plant with a lower raw water quality and using continuous chlorination at the intake formed more DBPs. In this plant, some non-regulated DBPs (e.g., dibromoacetonitrile and iodo-THMs) reached the product water in low concentrations (< 1.5 µg/L). Regulated THMs and HAAs were far below their maximum contamination levels set by the US Environmental Protection Agency. Substantial amounts of DBPs are disposed to the sea; low concentrations of DBPs were indeed detected in the water on shore of the desalination plants.